2020
DOI: 10.1186/s12984-020-00686-2
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and long-term effects of BCI-based rehabilitation of the upper extremity after stroke: a systematic review and meta-analysis

Abstract: Background: A substantial number of clinical studies have demonstrated the functional recovery induced by the use of brain-computer interface (BCI) technology in patients after stroke. The objective of this review is to evaluate the effect sizes of clinical studies investigating the use of BCIs in restoring upper extremity function after stroke and the potentiating effect of transcranial direct current stimulation (tDCS) on BCI training for motor recovery. Methods: The databases (PubMed, Medline, EMBASE, CINAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
161
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(171 citation statements)
references
References 100 publications
9
161
1
Order By: Relevance
“…For the FMA-UE, we again found improvement in three of four participants, but now two showed clinically meaningful differences (7 and 8 points). In fact, on average, there was a 4.5 point improvement in FMA-UE, which even compares well to longer training interventions [6].…”
Section: Clinical Assessmentsmentioning
confidence: 62%
See 1 more Smart Citation
“…For the FMA-UE, we again found improvement in three of four participants, but now two showed clinically meaningful differences (7 and 8 points). In fact, on average, there was a 4.5 point improvement in FMA-UE, which even compares well to longer training interventions [6].…”
Section: Clinical Assessmentsmentioning
confidence: 62%
“…Brain-computer interfaces (BCIs) that trigger game activity upon detection of movement-related brain signals, measured via electroencephalography (EEG), have received much attention over the last two decades [6,7]. These systems do not require active, volitional movement and can often just be driven by the imagination of movement, allowing them to be of benefit to those whose severe deficits preclude direct reinforcement of overt movement by closing the loop between the brain and the environment [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism may contribute to the recovery of motor function from hemiplegia after stroke. In fact, a recent BCI meta-analysis (Bai et al, 2020) showed that BCIs combined with neuromuscular electrical stimulation may be a better combination for functional recovery than other kinds of neurofeedback.…”
Section: Bci Training For Stroke Patientsmentioning
confidence: 99%
“…This paper offers a theoretical analysis, based on the literature, to answer these questions. Because BCIs have proven promising for upper limb rehabilitation ( Cervera et al, 2018 , Bai et al, 2020 ), we chose to focus on strokes affecting motor abilities of the upper limb, e.g., hemiplegia or hemiparesis.…”
Section: Introductionmentioning
confidence: 99%